2021
DOI: 10.1002/ggn2.10042
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, epigenetic, and post‐transcriptional basis of divergent tissue regenerative capacities among vertebrates

Abstract: Regeneration is widespread across the animal kingdom but varies vastly across phylogeny and even ontogeny. Adult mammalian regeneration in most organs and appendages is limited, while vertebrates such as zebrafish and salamanders are able to regenerate various organs and body parts. Here, we focus on the regeneration of appendages, spinal cord, and heart—organs and body parts that are highly regenerative among fish and amphibian species but limited in adult mammals. We then describe potential genetic, epigenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 180 publications
0
12
0
Order By: Relevance
“…Instead, appendage amputation of adult mammals often heals the wounding by the formation of a fibrotic scar [ 1 , 2 , 3 , 4 , 5 ]. The observation of the appendage regenerating process in vertebrates reveals that epimorphic regeneration shares conserved histological events, including re-epithelization of the wound, formation of the blastema and growth of the different tissues [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, appendage amputation of adult mammals often heals the wounding by the formation of a fibrotic scar [ 1 , 2 , 3 , 4 , 5 ]. The observation of the appendage regenerating process in vertebrates reveals that epimorphic regeneration shares conserved histological events, including re-epithelization of the wound, formation of the blastema and growth of the different tissues [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…After 7–10 DPA, the blastema derived from dedifferentiated tissue or existing progenitor cells emerges near the distal end of the rupture site and gradually differentiates to form a replacement appendage after 30 DPA [ 10 , 11 , 12 ]. Accordingly, the underlying cellular and molecular mechanisms that govern the reconstruction of multi-tissue structures are highly overlapped [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the role of agr2 in newt limb regeneration being established ( Kumar et al, 2007 ; Grassme et al, 2016 ) and elevated expression of ag1 and agr2 being shown during the regeneration of the frog ( Xenopus laevis) tadpoles limbs and tails ( Ivanova et al, 2013 ), it is still unknown whether these two genes also play critical roles in frogs’ regeneration abilities. Additionally, answering this question would contribute to a better understanding of whether the disappearance of ag1 in the evolutionary younger vertebrate species, in particular in mammals, could be one of the critical reasons for the sharp decline in their ability to regenerate body appendages ( Khyeam et al, 2021 ). Previously, we hypothesized and presented evidence that such a decline, as observed in groups of animals that appeared later in the evolution than amphibians, could be the result of the loss of some genes in their ancestors, which still regulate regeneration in the extant fishes and amphibians ( Ivanova et al, 2013 , 2015 , 2018 ; Korotkova et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This approach can also be important for regenerative medicine. The regenerative capacity is higher in simpler organisms [ 31 , 32 ]. Therefore, the controlled activation of earlier metazoan programs may facilitate injury healing and rejuvenation.…”
Section: Introductionmentioning
confidence: 99%